Corporate Governance and Earnings Quality in Chinese Manufacturing Industry - Dou, Chang (2019)
This paper selects 175 manufacturing companies listed on Shanghai stock exchange A-shares from 2014 to 2018 to study the influence mechanism of internal and external corporate governance on earnings quality. It is found that the ownership concentration, managerial compensation and analyst following are significantly correlated with earnings quality, while board characteristics have nothing to do with earnings quality.